Cytotoxic and antibacterial activities of biologically synthesized gold nanoparticles assisted by Micrococcus yunnanensis strain J2. (July 2018) - Jafari, Mandana; Rokhbakhsh-Zamin, Farrokh; Shakibaie, Mojtaba; Moshafi, Mohammad Hasan; Ameri, Atefeh; Rahimi, Hamid Reza; Forootanfar, Hamid
Abstract: In the present study the capability of Micrococcus yunnanensis J2 (isolated from Sarcheshme mine soil samples and identified by 16S rDNA sequencing) for biosynthesis of gold nanoparticles (Au NPs) was evaluated. The produced biogenic Au NPs were characterized using UV–visible spectroscopy, transmission electron microscopy (TEM), scanning electron microscopy (SEM), X-ray diffraction spectroscopy (XRD), thermal gravimetric analysis (TGA), and Fourier transform infrared spectroscopy (FTIR) methods. The related TEM and SEM images of biogenic Au NPs indicated spherical shaped and well dispersed nanostructures with the average particle size of 53.8 nm. Zeta potential analysis of as-synthesized Au NPs showed a peak at − 17.6 ± 1.8 mV. The XRD profile of the biogenic Au NPs contained five peaks positioned at 2θ of 38.2°, 45.8°, 63.7°, 77.6°, and 82.1° due to (111), (200), (220), (311), and (222) lattice planes, respectively, which clearly indicated the crystalline structure of the obtained Au NPs. Cytotoxic activity of biologically synthesized Au NPs (assisted by MTT-based colorimetric assay) revealed IC50 (µg/mL) of 73.6 ± 1.9, 85.6 ± 2.9, 63.5 ± 2.1, 65.2 ± 1.9, 105.3 ± 1.7, and 88.4 ± 2.1 against six cancer cell lines of U87, HT1080, PC12, Caco2, MCF7, and A549, respectively. However, two normal cells of 3T3 and Vero inhibited by 85% in the presence of 500 µg/mL of the biogenic Au NPs. Evaluation of antibacterial effect of the produced Au NPs and Au 3+ ions against three Gram-positive and four Gram-negative bacterial strains exhibited lower inhibitory activity of Au NPs compared to that of Au 3+ ions. Graphical abstract: a) mine soil samples were taken and screened for Au NPs producing bacterial isolate as observed on b) nutrient agar plate and c) scanning electron microscope (SEM). The selected isolate was cultivated and the culture broth was mixed by HAuCl4 (different concentration of 0.1, 0.5, and 1 mM) d) to synthesized Au NPs. e) Transmission electron micrograph and f) SEM image of the biogenic Au NPs were then prepared. fx1 Highlights: An Au NPs producer bacterium, Micrococcus yunnanensis J2, was screened. Higher cytotoxicity was obtained against cancer cell lines compared to normal cells. Antibacterial tests revealed higher inhibitory effect of Au 3+ ions compared to Au NPs.